Primary Ewing Sarcoma of Fronto-parietal Bone with Major Soft Tissue Extension: A Rare Case Presentation - Anshu Gupta (Current Overview on Disease and Health Research Vol. 1, 2022)
An 11-year-old girl appeared with an 8-month history of progressively worsening scalp swelling and no neurological deficits. A firm swelling appeared to be originating from the frontal bone on local examination. The results of the general and systemic examinations were normal. A well-defined lytic lesion in the left fronto-parietal bone with a subgaleal component was discovered on MRI. The patient was operated on, and the tumor was removed along with a skull reconstruction. A monomorphic tiny round cell tumor of bone was seen invading the subcutaneous tissue on histopathological investigation. The ultimate diagnosis of Ewing’s sarcoma was made after an immunohistochemical stain revealed diffuse immunopositivity for MIC-2 in tumor cells. The patient was kept for follow up for 3 months without any symptoms. The objective of this study is that one must consider the possibility of Primary Ewing sarcoma in a lytic lesion of the cranial bone in children and young adults.